New Therapeutic Approaches in Diabetic Retinopathy (The Review of Diabetic Studies, 2015)
Diabetic retinopathy is a common microvascular complication of diabetes mellitus. It affects a substantial proportion of US adults over age 40. The condition is a leading cause of visual loss. Much attention has been given to expanding the role of current treatments along with investigating various novel therapies and drug delivery methods. In the treatment of diabetic macular edema (DME), intravitreal pharmacotherapies, especially anti-vascular endothelial growth factor (anti-VEGF) agents, have gained popularity. Currently, antiVEGF agents are often used as first-line agents in centerinvolved DME, with recent data suggesting that among these agents, aflibercept leads to better visual outcomes in patients with worse baseline visual acuities. While photocoagulation remains the standard treatment for proliferative diabetic retinopathy (PDR), recent FDA approvals of ranibizumab and aflibercept in the management of diabetic retinopathy associated with DME may suggest a potential for pharmacologic treatments of PDR as well. Novel therapies, including small interfering RNAs, chemokines, kallikreinkinin inhibitors, and various anti-angiogenic agents, are currently being evaluated for the management of diabetic retinopathy and DME. In addition to these strategies, novel drug delivery methods such as sustained-release implants and refillable reservoir implants are either under active evaluation or have recently gained FDA approval. This review provides an update on the novel developments in the treatment of diabetic retinopathy.